DESIGNING SYSTEM INFORMATION E-FARMING BASED ON WEBSITE IN THE AGRICULTURAL SECTOR - Reza Andrea; Mika Debora Br Barus; Dito Aditia Darma Nasution; Nurhasanah (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The agricultural sector at this time is a commoditor contributing a very vital role in the cycle of human life needs. The impact of frequent changes in the level of harvest feasibility in the agricultural sector is increasingly becoming a challenge for the movement of economic growth, currently the level of feasibility of harvesting does not only occur on unproductive land but also penetrates into land with good productivity. Seeing the emergence of this statement, the analysis of the problem studied in this study is the need for the provision of an information system that can support the observation of the feasibility of crop yields to be produced by the agricultural sector, one of which is the E-Farming information system. information that can provide a statement of early detection of the occurrence of appropriate or inappropriate levels of crop yields in the agricultural sector. The data that makes up this information system are tabular data and spatial data, tabular data is numerical data from soil, plant and water availability data, while spatial data contains data on area, position of agricultural land. This information system is expected to be used by the general public, especially farmers, to find out whether their agricultural crops are feasible or not from anywhere, anytime, accurately and easily. The analysis method used in this research is Farming System Analysis (FSA), the method of developing an information system for assessing the feasibility of harvesting numbers in the agricultural sector using the System Development Life Cycle (SDLC) method using ERD diagrams, DFD, for modeling applications built and using Adobe Dreamweaver CS5 and MYSQL-Server as a database in the system.